Osebnostne lastnosti parov z zmanjšano plodnostjo - Bürger, Martina (Psihološka obzorja (Ljubljana), 1995)
The aim of the study was to find whether with regard to the efficient outcome of treatment infertile couples differ among themselves and from fertile couples by: personal history, personality structure, attitudes towardssexuality, pregnancy amd labour and by experiencing infertility. We compare two groups of infertile couples: in the first group there were the couples in whom artificial insemination - husband (AIH) failed and in the second the couples who achieved pregnancy in the first four AIH cycles. The control group consisted of fertile couples. We collected the data obtained from the medical history record, the questionnaire on the attitudes towards sexuality, pregnancy and labour (SSG), and the questionnaire on personality characteristics (MMPI-2). The obtained results showed that in schizoid personalities, prevailing in the first group, the unsuccessful outcome of treatment with AIH was more likely. To those couples sexuality, pregnancy, labour, and the child itself represented such an emotional excitement that they suppressed it to subconsciousness and to the somatic level of activity which contributed to infertility. In the second group the couples were more depressive and /or anancastic thus having a higher degree of possibility to conceive. Personality structure plays an important role in successful treatment of infertility which is also a psychosomatic problem and demands a holistic approach.
Keywords: neplodnost; zakonski pari; osebnostne lastnosti; zdravljenje; therapy; psihosomatika